2002
DOI: 10.1021/tx0200212
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of Hydroxylated Polychlorinated Biphenyls (PCBs)

Abstract: Polychlorinated biphenyls (PCBs) may be metabolized to hydroxylated compounds. While many of these metabolites are further converted to either the glucuronic acid or the sulfate conjugates by phase II enzymes, which facilitates their excretion, some hydroxylated PCBs persist in the body. This may reflect their inability to be conjugated. A possible role of uridine diphosphate glucuronosyl transferase (UGT) in the elimination of hydroxylated metabolites of PCBs was therefore investigated. Glucuronidation studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 37 publications
2
76
1
Order By: Relevance
“…Influence of a second flanking chlorine atom on the maximal rates of glucuronidation of polychlorobiphenylols in rat liver microsomes. Values taken from (Tampal et al, 2002) and (Daidoji et al, 2005). Concentrations of UDP-glucuronic acid (UDPGA) in channel catfish liver, proximal intestine and distal intestine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Influence of a second flanking chlorine atom on the maximal rates of glucuronidation of polychlorobiphenylols in rat liver microsomes. Values taken from (Tampal et al, 2002) and (Daidoji et al, 2005). Concentrations of UDP-glucuronic acid (UDPGA) in channel catfish liver, proximal intestine and distal intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronidation of several OH-PCBs has been studied in rat liver microsomes, with expressed human UGTs and in catfish intestinal and hepatic microsomes (Tampal et al, 2002;Daidoji et al, 2005;Sacco, 2006).…”
Section: Glucuronidationmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in workers exposed to the PCB have reported an increased incidence of liver tumors [185][186][187][188] . Some possible mechanisms by which PCB can cause cancer have been assumed: Reactive oxygen species (ROS) is produced through the enzymatic oxidation or autoxidation of PCB; PCB determines the increased expression of genes responsible for inflammation and apoptosis in the liver; and PCB has "toxic" effects on certain genes, such as the loss of part of a chromosome and chromosome breakage [189][190][191][192][193][194][195][196][197][198][199] . ROS are also able to reduce telomerase activity which can determine telomere shortening.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%